Luxury Marketing A Challenge for Theory and Practice - Wiedmann, Klaus-Peter.; Hennigs, Nadine; SpringerLink (Online service) (Wiesbaden : Gabler Verlag : Imprint: Gabler Verlag, 2013)
Luxury Marketing A Challenge for Theory and Practice The luxury market has transformed from its traditional conspicuous consumption model to a new experiential luxury sensibility that is marked by a change in how consumers define luxury. In a global context, it is crucial to understand why consumers buy luxury, what they believe luxury is, and how their perception of luxury value impacts their buying behavior. This handbook aims to provide a holistic approach to luxury marketing with respect to the characteristics and the key challenges and opportunities of luxury brand management. Therefore, the multifaceted contributions by authors from different parts of the world will offer both a research and management perspective of luxury marketing and deliver a concentrated body of knowledge with contributions from diverse elements. Contents Luxury Consumption - A Global Phenomenon or Dependent on Cultural Differences? - A Theoretical Perspective - The Context of Societal Change Luxury Brands - The Customer$1 (Bs Perspective within Specific Cultural Contexts The Luxury Industry - Counterfeits The Management of Luxury Brands Luxury Marketing in the Wine Industry Target Groups Academics and researchers in various disciplines; Marketing Managers. Editors Klaus-Peter Wiedmann is the Chair of Marketing and Management and the Director of the Institute of Marketing and Management at the Leibniz University of Hannover, Germany. Nadine Hennigs is an Assistant Professor at the Institute of Marketing and Management at the Leibniz University of Hannover, Germany.s
Luxury Consumption -- Luxury Brands -- The Luxury Industry -- The Management of Luxury Brands -- Luxury Marketing in the Wine Industry.
Keywords: Economics; Industrial management; Marketing; Economics/Management Science; Marketing; Management/Business for Professionals